(untitled) (TEL Tempo, Espaço e Linguagem, 2025)
References to everything related to the literary universe – works, authors, etc. – are frequent in Roberto Bolaño’s work. However, a closer look can also identify various representations and references to other products of artistic expression, from cinema to the visual arts. In the work of the same author, figurations of violence are also frequent. The relationship between these last two elements is the theme of this work. Therefore, we propose the observation of representations originating from cinema, photography and the visual arts that appear within Bolaño’s prose and that stand out for containing expressions of violence in its most extreme form. As a starting point, we have gore films and snuff videos, genres belonging to the audiovisual medium, but which can be expanded to also include photographic works and visual arts.